Analysis of Predictive Factors of Post-Covid-19 Associated Pulmonary Fibrosis: A Longitudinal Study - Shafi Muhammad, Faheem Ahmed Solangi, Abdul Salam, Akhtar Ali, Muhammad Hanif Chachar, Jagdesh Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the predictive factors related to the development and progression of pulmonary fibrosis in the patients who are COVID-19 infected. Study design: A cross-sectional study Place and Duration: This study was conducted at Ghulam Muhammad Mahar Medical College hospital Sukkur SMBBMU Larkana Pakistan from March 2021 to March 2022 Methodology: This study included patients admitted due to COVID-19 infection. The Presence of SARS-CoV-2 was confirmed by RT-PCR on the samples collected via nasopharyngeal swabs from suspected patients. CT severity score (CSS) was recorded for all the patients admitted, and their chest CT scans were conducted initially. Chest CT scans were performed during 3 and 6 months follow-upsto assess the progression of fibrotic abnormalities. Results: It was observed that out of 173 patients, male patients were 32.9% and 53.62 years was the mean age of patients. After the first CT follow up i.e., 3 months, pulmonary fibrosis was present in 52% of patients. Out of them, 62 patients had undergone a second CT scan, among which 66.1% patients had exhibited no significant signs of fibrotic findings whereas 33.9% patients had exhibited diminished lung fibrosis. Conclusion: In half of the COVID-19 patients, lung fibrosis was present and patients having severe pneumonia were more prone to developing pulmonary fibrosis.